Training/educational objectives and community development the Institute of Social Work and Community Development experience - Manalili, Angelito (1980)
The training design of the Institute of Social Work and Community Development is a classroom-practicum component. A laboratory community is chosen where the participants apply the theories they have learned in the classroom in pursuit of a thrust which is blending educational objectives and community development. Social investigation, consciousness raising, and the establishment of mechanisms for popular participation are among the strategies built into the training design to effect behavioral changes in the rural laboratory communities. To further enhance the efforts of the Institute in blending training objectives and community development it has conceptualized the Integrated Rural Social Laboratory Program, a collaborative concern of the Department of Community Development, the Department of Social Work, the Office of Continuing Education, and the Office of Research and Publication.
Keywords: Barangay Immersion Program; Community development; Social perception; Integrated Rural Social Laboratory Program; Leadership training